2016
DOI: 10.13181/mji.v25i3.1450
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of sepsis after open congenital cardiac surgery in infants: a pilot study

Abstract: ABSTRAK (80% vs 25%, RR=5,538, p=0,006). Secara statistik, gizi kurang (86% vs 84%, RR=1,059, p=1,000), timektomi (50% vs 76%, RR=0,481, p=0,157) ABSTRACTBackground: Postsurgical sepsis is one of the main causes of the high mortality and morbidity after open congenital heart surgery in infants. This study aimed to evaluate the role of cardiopulmonary bypass duration, thymectomy, surgical complexity, and nutritional status on postsurgical sepsis after open congenital cardiac surgery in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Fakhri et al 12 indicated in their study that the duration of CPB ≥ 90 min. was linked to a 5.538 increased risk of postsurgical sepsis in comparison to those ≤90 min.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Fakhri et al 12 indicated in their study that the duration of CPB ≥ 90 min. was linked to a 5.538 increased risk of postsurgical sepsis in comparison to those ≤90 min.…”
Section: Discussionmentioning
confidence: 95%
“… 3 , 6 Many are surgical site infections (incidence, 2.3%–8%). 7 Some are more severe, such as septicemia (incidence, 6.3%–15%), 8 , 9 , 10 mediastinitis (incidence, 0.2%–3.3%), 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 and endocarditis (incidence, 0.2%). 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR is a potential marker of inflammation to determine the presence of inflammation [12,13]. NLR was chosen because it is considered superior, frequently used, easy to calculate, and cheaper than other inflammatory markers [14]. However, until now, the use of NLR as a predictor in determining LCOS has not been widely reported.…”
Section: Original Articlementioning
confidence: 99%